2017
DOI: 10.1074/jbc.m116.753624
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cardiolipin Leads to Perturbation of Acetyl-CoA Synthesis

Abstract: Edited by George M. CarmanCardiolipin (CL), the signature phospholipid of mitochondrial membranes, plays an important role in mitochondrial processes and bioenergetics. CL is synthesized de novo and undergoes remodeling in the mitochondrial membranes. Perturbation of CL remodeling leads to the rare X-linked genetic disorder Barth syndrome, which shows disparities in clinical presentation. To uncover biochemical modifiers that exacerbate CL deficiency, we carried out a synthetic genetic array screen to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 83 publications
5
24
0
Order By: Relevance
“…A reduced sugar diet does not exacerbate the exercise intolerance of TAZ À/À mutants Due to evidence that low-sugar media is detrimental to CL knockout yeast (Raja et al 2017), we also measured the runspan of TAZ +/+ and TAZ À/À flies fed a 5% glucose diet. Reduced glucose availability had no detrimental effect on mutant endurance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A reduced sugar diet does not exacerbate the exercise intolerance of TAZ À/À mutants Due to evidence that low-sugar media is detrimental to CL knockout yeast (Raja et al 2017), we also measured the runspan of TAZ +/+ and TAZ À/À flies fed a 5% glucose diet. Reduced glucose availability had no detrimental effect on mutant endurance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the specific mechanisms leading to the metabolic changes in BTHS are unknown, they suggest that CL, long known to be required for oxidative phosphorylation and bioenergetics (2,3), is also required for optimal intermediary metabolism. This functional role is supported by studies in yeast strongly suggesting that CL deficiency leads to defects in the TCA cycle (32,33). Raja et al (32) showed that yeast cells that cannot synthesize CL (crd1⌬) exhibit decreased levels of acetyl-CoA.…”
mentioning
confidence: 85%
“…The absence of CL destabilizes AAC complex and its interaction with MRC supercomplexes, reducing the efficiency of mitochondrial ATP synthesis and its transport outside of mitochondria . A recent study has uncovered a role of CL in acetyl CoA biosynthesis via possible interaction with OMM localized acetyl CoA synthetase . Interestingly, CL deficiency also leads to defects in mitochondrial protein import pathways.…”
Section: Role Of CL In Mitochondrial Structure and Functionmentioning
confidence: 99%